Innovative Application of Nano-Organic Photochromic New Materials in Hakka Traditional Decorative Pattern Design - HuiJuan Lai (Advances in Materials Science and Engineering)
Hakka traditional decorative patterns are the epitome of local life and production customs, politics and economy, culture and art and other history and culture. The themes of Hakka traditional decorative patterns come from the real world or the imaginary world, expressing the expectation and beautiful vision of life. At the same time, it is also the essence of artists accumulated through life in the past dynasties, which has a certain impact on the integration of modern art design and traditional culture. Photochromic materials have the characteristics of reversible color change under the action of light. They have relevant applications in many fields, such as architecture, currency anti-counterfeiting, clothing decoration and so on. Firstly, this paper briefly expounds the Hakka traditional culture. According to the introduction of Hakka traditional culture, this paper leads to the design of Hakka traditional decorative patterns based on Hakka traditional culture, and discusses the decorative technology, decorative parts, application scope and development history of Hakka traditional decorative patterns. Secondly, this paper briefly summarizes the photochromic materials, and leads to the category, principle and mechanism of organic photochromic materials. In this paper, electrospinning technology is introduced, and relevant experiments are designed. The results show that the composites with MAPE have better flexural, compressive and impact strength when the length of carbon nanofibers changes consistently. In the bending performance comparison experiment, the experimental data show that the lowest value of the group with MAPE is 15MPa higher than the highest value without MAPE. In the comparative test of compressive properties, the experimental data show that there is a difference of 30MPa between the composites with MAPE and those without MAPE. Moreover, when the length of carbon nanofibers is 40um, the overall performance of the composites is the best. This paper takes the design of Hakka traditional architectural decoration pattern with nano organic photochromic new materials as an experiment. Experiments show that nano organic photochromic new materials have better properties than traditional building materials in flexural modulus, compressive modulus and thermal stability.